Evaluasi Kinerja Struktur Gedung Bertingkat Menggunakan Pendekatan Desain Berbasis Kinerja (Studi Kasus: Gedung Pendidikan Rangka Beton Bertulang 7 Lantai) - Saifulloh Fatah Pangestu; M Mirza Abdillah Pratama (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2021)
In Indonesia, earthquake-resistant structures are governed by SNI as design codes, which are updated on a regular basis. As a result, existing buildings with outdated requirements must be reviewed so that the building's performance may be assessed in light of the most recent codes. Pushover analysis and direct displacement-based design are used to characterize the real condition of the building in order to assess its performance. The 7-story reinforced concrete building structure in this study was designed according to SNI 03-2847-2002 and SNI-1726-2002. This structure will be evaluated utilizing the FEMA 440 and FEMA 356 procedures, as well as SNI 1726:2019. The results show that the structure meets the minimal performance limit criteria (which is life safety) in terms of displacement and drift values from the pushover analysis, based on FEMA 356 and FEMA 440 performance levels. The evaluation indicates better structural response parameter values (R, Ω0, and Cd) than that of SNI 1726:2019, indicating that the building performance is good and capable of withstanding the design earthquake load.